2011
DOI: 10.5194/acp-11-4353-2011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pollutants and their correlation to meteorological conditions at a suburban site in the North China Plain

Abstract: Abstract. North China Plain (NCP) is one of the most densely populated regions in China and has experienced enormous economic growth in the past decades. Its regional trace gas pollution has also become one of the top environmental concerns in China. Measurements of surface trace gases, including O 3 , NO x , SO 2 and CO were carried out within the HaChi (Haze in China) project at Wuqing Meteorology Station, located between 2 mega-cities (Beijing and Tianjin) in the NCP, from 9 July 2009 to 21 January 2010. De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(153 citation statements)
references
References 48 publications
5
136
1
Order By: Relevance
“…They compared the characteristics of dispersion and transport during pre-episode and episode days. Xu et al (2011) confirmed the deterministic impact of wind speed and wind direction on the concentration of various trace gases at a suburban site between two mega-cities. Csavina et al (2014) examined dust events in two semi-arid sites and then showed a complex, nonlinear dependence of PM 10 (particulate matter with aerodynamic diameters ≤ 10 µm) on wind speed and relative humidity.…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 53%
See 2 more Smart Citations
“…They compared the characteristics of dispersion and transport during pre-episode and episode days. Xu et al (2011) confirmed the deterministic impact of wind speed and wind direction on the concentration of various trace gases at a suburban site between two mega-cities. Csavina et al (2014) examined dust events in two semi-arid sites and then showed a complex, nonlinear dependence of PM 10 (particulate matter with aerodynamic diameters ≤ 10 µm) on wind speed and relative humidity.…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 53%
“…ern China, and the degree of air pollution in the region is largely subject to large-scale atmospheric conditions (Xu et al, 2011). In some other regions, strong links between the concentration of aerosols and certain synoptic weather condition have already been identified (Demuzere et al, 2009;Saavedra et al, 2012).…”
Section: Y Zheng Et Al: Impact Of Atmospheric Circulations On Aementioning
confidence: 99%
See 1 more Smart Citation
“…For chemical reactions and transformations, temperature, solar radiation, and humidity are the most crucial factors [24,25]. However, no clear linear relationships can be found between meteorological parameters (i.e., wind speed, ultraviolet radiation, or temperature) and the concentration of pollutants [26,27]. Furthermore, due to topographical differences, the key meteorological parameters that may affect the haze process are distinct in different regions.…”
Section: Introductionmentioning
confidence: 94%
“…However, urban area only takes up approximately 5% area in China while cropland is the dominant surface type also featuring dense population and high PM2.5 exposure (Liu, 2005;Xu et al, 2011). Frequent regional-scale haze pollution and cropland-dominant land cover in China make 15 it necessary to figure out this interaction over rural area Zhao et al, 2013b).…”
Section: A Comparison Of the Dome Effect Over Urban And Rural Areasmentioning
confidence: 99%